Disproving the myth of racial harassment and trauma among Indonesian Americans - Salama, Nadiatus; Fanani, Muhyar; Pohl, Florian; Widiastuti, Widiastuti (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2022)
Racial trauma among Asians, including Indonesians, has increased dramatically in the United States. While many studies have been written about the significance of recurring race-related traumatic incidents, the broader meaning of the unexpected and dark side of racial trauma experiences among Indonesians who reside in the United States is under-reported. This study aims to explore the meaning of experience dealing with racial trauma among Indonesians living in the United States using a qualitative phenomenological approach. We conducted in-depth interviews via the Zoom platform with a nationally representative purposive sample of 16 adults aged 26 and older. In analyzing this phenomenological study, all stages of phenomenological reduction were used. The findings demonstrate that racial trauma among Indonesian Americans can be categorized into three themes: 1) feeling sad and angry, 2) being exhausted, and 3) suffering physically. Therefore, the myth that Asian Americans are immune to racism and its effects is not necessarily true. This study also offers implications for future research on racial understanding and discussion.